Consumer credit models pricing, profit, and portfolios - Thomas, L. C. (Oxford : Oxford University Press, 2009)
This text reviews the current methodology and measures used in credit scoring and then looks at the models that can be used to address new challenges.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Credit scoring systems; Credit control -- Methodology